Gender and sexualities in contemporary communication policies in Argentina - Justo Von Lurzer, María Carolina (2017)
In recent years Argentina went through a process of public debate over communication policies which resulted in the enactment of the Audiovisual Communication Services Law in 2009 and the creation of public bodies in charge of applying and monitoring the Law. Questioning the social role of media, its economic structure and regulatory framework, introduced issues, perspectives and knowledge which had up to then been the exclusive domain of the communication and culture fields. These debates took place simultaneously with the advances in issues related to sexual rights and gender, which materialized in laws (Equal Marriage Law ,Violence against Women Law, Gender Identity Law, to only mention a few) and introduced the discussion on the role of mass media in the reproduction of discriminatory cultural patterns and the exercise of symbolic violence against women. From the analysis of current legislation, this paper attempts to explore the potentialities and limitations of its implementation and media theories that support it. Also, the centrality of “media text” - as object of analysis, as object of complaint and as object of regulation – inasmuch as this new role is in tension with the consensus on the cultural study of audiovisual media.